Characterizing Woody Breast Myopathy in a Meat Broiler Line by Heat Production, Microbiota, and Plasma Metabolites - Maharjan, Pramir; Hilton, Katie; Weil, Jordan; Suesuttajit, Nawin; Beitia, Antonio; Owens, Casey M.; Coon, Craig (Frontiers in Veterinary Science, 2020)
Selection for quantitative traits in meat broilers such as breast yield and growth rate exert physiological pressure leading to ante mortem histological and biochemical alterations in muscle tissues. The poultry industry has recently witnessed a myopathy condition affecting Pectoralis major (breast muscle) of broilers, called woody breast (WB), an etiology still unclear to scientific community. A study was conducted to characterize the WB myopathy in a meat broiler line at its finishing phase (d 41) in terms of heat production (HP), microbiota and plasma metabolites. Two treatment groups were studied – WB affected (myopathy) and normal (non-myopathy) broiler; n=20 in each group. Indirect calorimetry was utilized for HP measurement. Furthermore, body composition (BC) analysis was also performed using dual-energy x-ray absorptiometry (DEXA). Microbiota in ileal digesta was studied with PCR amplified 16s rRNA gene. LC-MS targeted metabolomics was performed to understand differential expression of plasma metabolites. Results showed that there was difference in fasting HP (P < 0.05) between these two treatment groups, with non-myopathy broiler producing more heat which was indicative of higher body protein content validated by higher protein: fat ratio by BC results. Less protein content in myopathy bird could be due to probable higher mixed muscle degradation occurring in lean tissue as marked by elevated 3-methylhistidine expression in plasma. Microbiota results showed unclassified Lactobacillus as predominant genus with higher abundance occurring in myopathy group; whereas at species level, L. acidipiscis was predominant bacteria for non-myopathy broiler. Differentially significant metabolites (P < 0.05) identified from plasma metabolome between these two treatment groups were homocysteine, cyclic GMP, trimethylamine N-oxide (TMAO), tyramine, carnitine and acetylcarnitine, which were all associated to cardiovascular system. The findings suggest that more research in meat broilers could be opted towards delivering reduced vascularity issues to alleviate this myopathy condition.